"I Just Have to Do What I Can": "Mobile Suit Gundam 0079" and the Burdens of War - Sylvia Duvenary (The Toro Historical Review, 2023)
The implications of the Asia-Pacific War persisted throughout the 20th century. Since 1945, Japan found itself in an endless conflict between various approaches at remembering the war and had to deal with the ways that these memories pervade public life. The 1970s saw a resurgence of pro-nationalist media, specifically in animation. As an entertainment medium, animation has proven itself to be a popular and receptive outlet for both creative and political expression. In 1979, Tomino Yoshiyuki's Mobile Suit Gundam 0079 first aired in Japan, which launched the Mobile Suit Gundam series. Gundam's historiography consists of analyses of the cinematic remakes of Mobile Suit Gundam 0079, close examinations of later entries, and a thematic approach of the entire series. This paper builds upon the argument that Gundam is a critique of war, and that Tomino specifically criticizes Imperial Japan's policies in the Asia-Pacific War, unlike industry contemporaries. By analyzing selections from the original Mobile Suit Gundam 0079 television series, focusing on major and minor side characters, and connecting this analysis with the experiences of Japanese soldiers during the war, Tomino makes his views apparent to the audience. A conversation between Gundam 0079's protagonist's father and a soldier that would later become an important part of the show and an examination of the main cast of teenage characters as they begin their journey, reveal Tomino's opinions towards the use of child soldiers, a "filler" episode of a rogue soldier protecting a group of defenseless children he previously traumatized illustrates the power of war guilt, and a brief profiling of a major character in the show touches upon the agony of involuntarily participating in war.